Socioeconomic impacts of flooding in South-Eastern Nigeria: Causes, coping strategies, and flood control measures - Obiwulu, Ifenna; Syahreza, Saumi; Oktari, Rina Suryani (Publisher of Widyagama University of Malang (UWG Press), 2023)
The occurrence of floods in Nigeria, particularly in the South-Eastern zones, has resulted in significant socioeconomic losses and continues to be a recurring hazard. This study aims to investigate the socioeconomic impacts of flooding in the region, identify causes and coping strategies, suggest measures for flood control, and evaluate the role of the government in flood management. The study collected data through a questionnaire distributed to 200 respondents and analyzed it using simple percentages, frequency distribution tables, and bar charts. The findings reveal that the incidence of flooding has a significant impact on the socioeconomic activity of the affected communities. To address this issue, proactive and reliable measures are necessary, such as reviewing urban plans and policies, establishing state response desks and relief centers in flood-prone areas, etc. These steps can provide long-term results and promote socio-economic growth in the region. Overall, the study highlights the need for effective flood management strategies to minimize the negative effects on communities and foster sustainable development in Nigeria. JEL Classification J10; J18; J19